إقرار السلطة العقابية للهيئات الإدارية المستقلة - صوالحية، عماد (جامعة العربي التبسي تبسة, 2017)
Administrative sanctions are an urgent necessity for the organization of social life and the realization of economic security. It is a means imposed by practical requirements and granted to the independent administrative bodies; and this body represent the adversary and the arbitrator at the same time, and the person is obliged to conform and submit, for the purpose of imposition is to ensure the efficiency of administrative work in parallel with respect and the protection of rights and public freedoms, and also the punitive power granted to the independent administrative bodies, went through several stages before being adopted in the institutional bodies of the states.
الجزاءات الإدارية ضرورة ملحة لأجل تنظيم الحياة الاجتماعية وتحقيق الأمن الاقتصادي، فهي وسيلة فرضتها مقتضيات عملية ومنحتها للهيئات الإدارية المستقلة، حيث تحولت هذه الأخيرة وهي بصدد ممارسة هذا الاختصاص إلى خصم وحكم في ذات الوقت، ويكون الفرد مجبر على الإذعان والخضوع لها، لأن الغاية من فرضها هي تحقيق فاعلية العمل الإداري بالموازاة مع احترام وحماية الحقوق والحريات العامة، حيث يكون ذلك الاحترام نابع من الهيئات الإدارية المستقلة ذاتها دون أن ننتظر أن يقومها القضاء حتى تكون هناك ثقة للأفراد بها، فهذه السلطة العقابية الممنوحة لها، لم تأتي من العدم بل مرت بعدة مراحل قبل أن يتم اعتمادها في الجهاز المؤسساتي للدول.
Keywords: القوانين والتشريعات -- السلطات العقابية -- الهيئات الإدارية -- العقوبات الإدارية